A molecular phylogeny and revised higher‐level classification for the leaf‐mining moth family Gracillariidae and its implications for larval host‐use evolution. (13th October 2016) - KAWAHARA, AKITO Y.; PLOTKIN, DAVID; OHSHIMA, ISSEI; LOPEZ‐VAAMONDE, CARLOS; HOULIHAN, PETER R.; BREINHOLT, JESSE W.; KAWAKITA, ATSUSHI; XIAO, LEI; REGIER, JEROME C.; DAVIS, DONALD R.; KUMATA, TOSIO; SOHN, JAE‐CHEON; et al.
Abstract: Gracillariidae are one of the most diverse families of internally feeding insects, and many species are economically important. Study of this family has been hampered by lack of a robust and comprehensive phylogeny. In the present paper, we sequenced up to 22 genes in 96 gracillariid species, representing all previously recognized subfamilies and genus groups, plus 20 outgroups representing other families and superfamilies. Following objective identification and removal of two rogue taxa, two datasets were constructed: dataset 1, which included 12 loci totalling 9927 bp for 94 taxa, and dataset 2, which supplemented dataset 1 with 10 additional loci for 10 taxa, for a total of 22 loci and 16 167 bp. Maximum likelihood analyses strongly supported the monophyly of Gracillariidae and most previously recognized subfamilies and genus groups. On this basis, we propose a new classification consisting of eight subfamilies, four of which are newly recognized or resurrected: Acrocercopinae Kawahara & Ohshimasubfam. n. ; Gracillariinae Stainton; Lithocolletinae Stainton; Marmarinae Kawahara & Ohshimasubfam. n. ; Oecophyllembiinae Réal & Balachowsky; Parornichinae Kawahara & Ohshimasubfam. n. ; Ornixolinae Kuznetzov & Baryshnikovastat. rev. ; and Phyllocnistinae Zeller. The subfamily Gracillariinae is restricted to the monophyletic group comprising Gracillaria Haworth and closely related genera. We also formally transfer Acrocercops scriptulata Meyrick to Ornixolinae and use the name Diphtheroptila Vári, creating Diphtheroptila scriptulata comb. n. An exploratory mapping of larval host‐use traits on the phylogeny shows strong conservation of modes of leaf mining but much higher lability of associations with host plant orders and families, suggesting that host shifts could play a significant role in gracillariid diversification. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:942814A2‐DE66‐41D4‐8AB6‐FF0B18C87EDB .